Regulatory uncertainty and TARP - Lin, Yupeng; Liu, Xin; Srinivasan, Anand (Journal of Financial Stability, 2025)
Using the Troubled Asset Relief Program (TARP) as a laboratory, this paper examines the impacts of bank bailouts on bank-dependent clients. We find that large TARP recipient banks reduce credit supply to dependent borrowers in the post-TARP period. A large fraction of credit supply reduction is due to regulatory uncertainty on account of an increased likelihood of fines. Liquidity hoarding by TARP banks also drives part of the reduction in credit supply. Relationship borrowers experience a valuation loss around the announcements of their main banks’ TARP approvals consistent with a credit supply reduction.